2016
DOI: 10.1097/mib.0000000000000629
|View full text |Cite
|
Sign up to set email alerts
|

A Controlled Study of a Group Mindfulness Intervention for Individuals Living With Inflammatory Bowel Disease

Abstract: Results demonstrate the feasibility, acceptability, and efficacy of a mindfulness intervention for patients with inflammatory bowel disease, with medium-to-large effects on psychological distress, quality of life, and mindfulness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 43 publications
3
48
0
1
Order By: Relevance
“…A recent study comparing MBT to waitlist control found that the mindfulness group reported significant improvements in anxiety, quality of life, and depression when compared to the control group. 75 This study also found that these effects persisted at 6-month follow-up. Other studies have produced compelling but less clear results.…”
Section: Mindfulnesssupporting
confidence: 62%
“…A recent study comparing MBT to waitlist control found that the mindfulness group reported significant improvements in anxiety, quality of life, and depression when compared to the control group. 75 This study also found that these effects persisted at 6-month follow-up. Other studies have produced compelling but less clear results.…”
Section: Mindfulnesssupporting
confidence: 62%
“…7,8 Many groups have explored the benefits of educational interventions on patient knowledge, including prior studies of workshops, lectures, handbooks, group sessions, and face-to-face instruction. [12][13][14][15][16][17] One of the first studies, done across 9 communities in the United States, offered workshops with associated questionnaires and face-to-face sessions with patients and their families. 4 Although less than 10% of participants completed all questionnaires, significant improvements were demonstrated in participants' IBD knowledge, which were maintained for at least 3 months.…”
Section: Introductionmentioning
confidence: 99%
“…This project includes different professionals interacting to create an integrated exchange of competences. Patients can therefore take advantage of gastroenterological, surgical together with psychiatric check-ups, as well as psychological counseling with cognitive-behavioral orientation, for the most part based on the mindfulness approach ( 79 ). In our experience, in less than 2 years the GE.Co Project has involved about 50 patients which have been receiving both pharmacological and psychological treatment.…”
Section: Ethics and Disseminationmentioning
confidence: 99%